Adaptation and Mitigation on Climate Change Through Collaboration Between Local Municipal and Community Participation in DKI Jakarta - Yolanda, Francis; ., Rita; ., Citra; Hariyani, Frieda; Aria Wijaya, Firdhan; ., Novrizal (KnE Social Sciences, 2019)
An anthropogenic and natural cause has contributed significantly to the increases in temperature globally. A wide range of actions from institutional and social level can be done as the response to these changes. This study explores the ability of adaptation and mitigation in terms of governmental-social-ecological using lessons from the specific case study. As a metropolitan city, Jakarta is examined as one of the most vulnerable cities to climate change risk. By using observation approach through the interview, this case study focuses on climate village program which integrated the participation of people who reside in Jakarta and local government effort, as a domestic part in term of supporting green gas emission reduction. Keywords: climate change, adaptation, mitigation